Privilege, power and performativity: the ethics of mathematics in society and education - Paul Ernest (Universidade Federal do Oeste da Bahia, 2021)
The undoubted benefits and intrinsic virtues of mathematics should not blind us to potential collateral damage as the huge juggernaut of mathematics rolls over education and society towards a reshaped future. Because of its great power and influence across the whole of society we need to undertake an ethical audit. This paper conducts an ethical critique that considers four interrelated aspects of mathematics in education and society and their negative impacts. 1. The overvaluation of mathematics and the effects this power has in maintaining privileges. 2. The powerful negative impacts of mathematical studies have on many individual learners. 3. Visible but problematic applications of mathematics within society that are shielded from criticism because mathematics continues to be viewed as neutral. 4. The profound and performative effects of the hidden applications of mathematics that reformat society and change our everyday lives but remain unchecked in every sense. Most of the paper is devoted to revealing these damaging effects. The solutions proposed are for ethical awareness to be fostered in mathematical study at all levels, as well as challenging the widespread stereotype of mathematics as ethically neutral.